Cascade intramolecular imidoylation and C–H activation/annulation of benzimidoyl chlorides with alkynes: one-pot synthesis of 7H-dibenzo[de, h]quinoline analogues. Issue 49 (3rd June 2019) - Liu, Jiao; Fang, Hao; Cheng, Rui; Wang, Zhishuo; Yang, Yudong; You, Jingsong
Abstract : Described herein is a cascade Lewis acid-promoted intramolecular Friedel–Crafts-type imidoylation and Rh(iii )-catalyzed C–H activation/annulation of benzimidoyl chlorides and alkynes, providing a divergent synthetic shortcut to 7 H -dibenzo[ de, h ]quinoline analogues. Abstract : Reported herein is a cascade Lewis acid-promoted intramolecular Friedel–Crafts-type imidoylation and Rh(iii )-catalyzed C–H activation/annulation of benzimidoyl chlorides and alkynes, providing a general and concise one-pot approach to 7 H -dibenzo[ de, h ]quinoline analogues. This divergent approach is based on a convergent retrosynthetic disconnection strategy.